INTERCULTURAL SPACES IN TEACHING ENGLISH AS A FOREIGN LANGUAGE TO ELEMENTARY SCHOOL IN BRAZIL - São Pedro, Joana de (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract This work is part of my doctoral research in Brazil. I have been investigating the presence of Intercultural Spaces in the English lessons in an Elementary School from the perspective of the teacher. Thus, it is a Case Study in which lesson observations will be compared to the teacher’s discourse about her own practice (Cohen, Manion & Morrison, 2011). It is a study of a single teacher practice and the students are not participants. The definition of Intercultural Spaces is based on Bhaba’s concept (1994), Kostogriz’s definition (2005) applied to Second Language Acquisition, Kramsch’s idea (2009) in the context of Foreign Language Learning and Widin and Yasukawa’s study (2013) when it comes to teacher’s role of creating such types of Intercultural Spaces in the classroom. Hence, as background to this research, it is believed that students in Early Elementary School, who are between seven and ten years old, should be educated as critical and ethical citizens (Morin, 2005; Menezes de Sousa, 2011; Rocha 2012). Thus, I expect to contribute to Teacher Education with this research in the light of New Learning (Cope & Kalantzis, 2012). Resumen Este trabajo es parte de mi investigación de doctorado en Brasil.Estoy analizando la presencia de espacios interculturales en las clases de inglés de un colegio de enseñanza primaria desde la perspectiva de una profesora. Es un estudio de caso en el cual las observaciones de clase se compararán al discurso de la profesora con respecto a su propia práctica (Cohen, Manion & Morrison, 2011). Asimismo, es un estudio de la práctica de una única profesora y los alumnos no participan en la investigación. La definición de Espacios Interculturales se basa en el concepto de Bhabha (1994), en la definición de Kostogriz (2005) aplicada a la adquisición de segundas lenguas, en la idea de Kramsch (2009) en el contexto de enseñanza de lengua extranjera, y en el estudio de Widin y Yasukawa (2013) en lo que concierne al papel de la profesora de crear tales espacios interculturales en la clase. Como telón de fondo de este trabajo, se cree que los alumnos de enseñanza primaria que tienen entre siete y diez años deberían ser formados como ciudadanos críticos y éticos (Morin, 2005; Mendez de Sousa, 2011; Rocha, 2012). Con este trabajo inspirado en el Nuevo Aprendizaje (Cope & Kalantzis, 2012), espero contribuir a la formación de nuevos profesores.